Fixed point results for convex orbital nonexpansive type mappings - Llorens-Fuster, Enrique (Topological Methods in Nonlinear Analysis, 2024)
We define some classes of generalized nonexpansive mappings under assumptions concerning the convex combinations of two consecutive points in their orbits. For these mappings, in the setting of Banach spaces that enjoy normal structure, we provide several fixed point results.